Uncaria tomentosa: possível uso como adjuvante no tratamento do câncer cólon retal - Farias, Iria Luiza Gomes (2011)
Reports of the use of cat's claw (Uncaria tomentosa) in patients with cancer, in conjunction with traditional therapies such as chemotherapy and radiotherapy, show decrease in adverse effects to these therapies (such as hair loss, weight loss, nausea, secondary infections, and skin problems). Subsequent research showed that cat's claw may help in the restoration of cellular DNA, preventing cell damage caused by chemotherapy; it also acts as an immunomodulator and antioxidant. Studies also show that cat's claw may have a direct effect in stimulating myeloid. The therapeutic dose of chemotherapy is often limited by toxicities, neutropenia being the most observed at high risk of infection. Pharmacological interventions able to reduce or prevent adverse effects may have a substantial impact on the treatment of cancer. In this context, it follows the objectives of this research: to study the pathophysiology of colorectal cancer and evaluate the effect of Uncaria tomentosa, used as an adjunct in the treatment of colorectal cancer in hematological, immunological, oxidative stress and DNA damage. The results (i) confirm previous studies that indicate the influence of the immune system in the evolution of colorectal cancer and showed the relative risk of poor clinical response of the group of women, since they have lower levels of T CD8+ cells and low hemoglobin levels; (ii) it showed that the adaptive process of tumor cells to glycolytic metabolism as a result of poor oxygenation, resulting in increased lipid peroxidation measured by TBARS content and that this parameter is not an early indicator of clinical response, (iii) it proves that Uncaria tomentosa has the property of stimulating myeloid proliferation, similar to colony stimulating factor of granulocytes, being effective in recovery from neutropenia induced by chemotherapy in animal models, (iv), although, in the dose of 300 mg of dry extract per day, Uncaria tomentosa was not effective in altering the immune response, in improving the levels of oxidative stress and in reducing DNA damage, and in minimizing the side effects of chemotherapy of colorectal cancer patients. The Uncaria tomentosa is efficient in reducing neutropenia caused by chemotherapy, by stimulate the proliferation of myeloid precursors, further studies are needed to determine in which treatment regimens its use may be effective.